Acquiring skills and attributes necessary for employment in junior administrative roles : a thesis presented in partial fulfilment of the requirements for the degree of Master of Education in Adult Education at Massey University - Dean, Janine (Massey University, 2005)
Tertiary pre-employment skills based programmes are designed to assist students in gaining the skills and academic qualifications needed to gain employment. This study explores the skills and attributes needed to gain employment in the business administration field. It explored this from the perspective of students and also from prospective employers' points of view. This research included a review of literature within the field of study and also focused on the delivery, material and outcomes of some business administration programmes. The teaching rationale of one polytechnic was also included as it showed how the way students learn and the desired outcomes have influenced the method of delivery. Integral to this study was the use of questionnaires that students and prospective employers filled out, and interviews with three employers and three students. This brought to light their views on skills and attributes, along with what they perceived as being important in gaining and giving employment opportunities. The research makes recommendations, from an educator's perspective, on what is required to enhance students' opportunities for employment within this field, and how programmes can be developed to allow opportunities for students to develop skills and attributes valued in business occupations.
Keywords: Whitireia Community Polytechnic; Business education; Office practice; Technical institutes -- Curricula; New Zealand -- Porirua; Study and teaching